43‐1: Automotive Autostereoscopic 3D Display. Issue 1 (28th June 2021) - Kreuzer, Markus; Pross, Achim; Ewen, Christoph; Song, Kiuk; Purzycki, Adam
Abstract : The new S‐Class introduced a newly developed 3D instrument cluster display as one of its highlights. The display enables real depth perception without the need for glasses and without compromising visual quality. This paper describes the requirements, system design and technical realization of a fully position‐adaptive autostereoscopic display.